Effect of GaAs (100) substrate surface reconstruction on magnetic properties of Ni thin films - (:unkn) unknown (ELSEVIER, 2015)
Effects of (4 x 6) and (2 x 4) reconstructed surfaces of GaAs (100) substrate on magnetic properties have been investigated for nickel thin films by using ferromagnetic resonance technique. The films were grown by molecular beam epitaxy in ultrahigh vacuum condition, with 20-40 nm thickness range. X-ray diffraction measurements showed that all films have a single crystalline structure. In the film plane the nickel films exhibited a combination of two fold and four fold anisotropy induced by unsatisfied tetrahedral bonds of Ga and As rows oriented along [110] and [1 (1) over bar0] directions. Effects of different reconstructions on magnetic anisotropies were discovered to be more dominant in the film normal. The physical mechanisms responsible for the observed surface reconstruction and thickness dependence of magnetic anisotropy are discussed in detail. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ni thin film; GaAs (100); Magnetic anisotropy; Ferromagnetic resonance; Reconstructed surface; FE